Lisboa Story de Wim Wenders. El descubrimiento de la ciudad como metáfora del arte cinematográfico. A la búsqueda de sus identidades - Monterrubio Ibáñez, Lourdes (Revista de Filología Románica, 2011)
To re-discover the cinematographic look through the revelation of the unknown city, its images, its sounds, its music, its literature, its identity. In the centenary of the cinema, and of its possible and premature death, the discovery of an unknown city can mean the renovation of the artistic lost look. The identity of the city of Lisbon as a indispensable space for the reunion of the filmmaker with a new creative impulse.